Significados del cuerpo en personas con Diabetes Mellitus en la ciudad de Cali (2018)
This investigation arose as part of the experiences of family health interventions; it was performed with four people diagnosed with diabetes mellitus seeking to know the meanings of the body from disease and relationships with significant others, including the doctor. Methodology was qualitative and developed through in-depth interviews. The main results highlighted the body meaning as constitutive, temporal and physical that allows access to the world and as a device symbolic action, communication and human language, is built on the relationship with the other, with whom our identity is consolidated and aesthetically regulated body image. It concluded that when the body is sick, body experimentation and the resulting notion of it changes, not only for the physical and subjective feelings of human beings, but by the social constructions that are made of body and disease.